President's Cabinet Report 2015 Q1 - STLR (My University, 2021)
This document defines transformative learning and STLR, and describes the details for the pilot program. Accompanied by slides for presentation.
Keywords: Transformative learning; Pilot program; University of Central Oklahoma--(OCoLC)fst00677219; Marketing--(OCoLC)fst01010167; Transformative learning--(OCoLC)fst01743611; College student development programs--(OCoLC)fst00867959; Training--(OCoLC)fst01154445